DIFFERENTIAL EXPRESSION OF INDUCED RESISTANCE GENES BY ABSCISIC ACID (ABA) AGAINST POTATO EARLY BLIGHT DISEASE - EL-Argawy, Eman; Adss, Ibrahim A; Bayoumi, Shokry R (Potato Journal, 2017)
Abscisic acid (ABA) enhanced disease resistance of two potato cultivars, Nicola and Spunta, against early blight disease. Treatment with ABA solution (10 ÂµM) reduced the disease severity in both cultivars compared to the untreated infected plants. Differential display gene analysis for treated plants revealed three clear bands. These bands showed significant homology to well-known genes in the GenBank database and identified as superoxide dismutase (CuZnSOD), WRKY transcription factor (StWRKY) and endoglucanase from potato genome. RT-PCR showed an increase in the expression (activity) level of CuZnSOD and WRKY genes in ABA treated plants compared to the untreated plants.